A two-step process for indigo production from Baphicacanthus cusia stem. (10th November 2022) - Jiang, Yipeng; Xiao, Ying; Wang, Zikang; Yu, Hao; Hu, Kun; Zhang, Tian-Ao; Hu, Jiajun; Gao, Min-Tian
Abstract: The feasibility of using Baphicacanthus cusia ( B. cusia ) stem as raw for indigo production was investigated. B. cusia stem and leaf both contain the indigo material precursor, indican, but little indigo was produced from stem by the conventional fermentation process. The release of indoxyl and indican, the formation of indigo and the activity of β-glucosidase in stem material were determined, to find a way to produce indigo from B. cusia stems. High temperature had little effect on the formation of indigo, but it reduced endogenous β-glucosidase activity, resulting in extensive release of indican from stems. Microwave drying of stems greatly increased subsequent indican extraction with aqueous ethanol, by rapid heating, which inactivated endogenous β-glucosidase. Indigo production by enzymic hydrolysis of extracted indican increased the mass yield of indigo 1.36-fold. This two-step process maximizes B. cusia biomass utilization and provides a more efficient indigo production process. Graphical abstract: Image 1 Highlights: Indican in B. cusia stems could not be converted into indigo during conventional fermentation. Stem β-glucosidase was the key factor preventing high-yield indican extraction. Stem β-glucosidase inactivation by microwave drying markedly improved indican extraction. Microwave drying allowed long-term stem storage and markedly increased indigo production yield. A two-step microwave drying/indican extraction process was proposed for indigo production.